Gender and the tax compliance puzzle: does gender influence taxpayers' behaviour towards tax compliance? Evidence from Rwanda - Daniel Twesige; Eugene Rutungwa; Gasheja Faustin; Isaie Kadhafi Misago; Samuel Mutarinda (Cogent Business & Management, 2024)
This study analyzed whether gender is an important factor in explaining the behaviour of taxpayers towards tax compliance. The study extended the theory of planned bahaviour to establish the factors influencing the behaviour of taxpayers towards tax compliance across gender. Primary data was collected from 390 taxpayers using a closed-ended questionnaire set. Descriptive and inferential statistical tools were used to analyze the data. Descriptive data were presented using the mean and standard deviation, while inferential data were analyzed using a multivariate regression analysis and a univariate and independent t-test. Findings from the survey showed that the predictor variables contribute 51% in explaining the taxpayers towards tax compliance of which 84.23% is for male taxpayers while 71.86% is for female taxpayers. The results further revealed that there is a statistical difference in the behaviour of taxpayers towards tax compliance. Female taxpayers are more influenced by tax knowledge, perception of government spending and roles of tax authority while male taxpayers are more influenced by tax penalties, economic factors and tax rates. Gender contributes 55.1% to taxpayers' beheviour towards tax compliance. The study contributed to the current literature by establishing the predictor variables that influences the behaviour of taxpayers towards tax compliance which can be used as a basis when designing a tax compliance policy and program.
Keywords: E62; H20; H26; H30; H31; H32; H39; 650; Gender; tax; tax compliance; tax beheviour